1995
DOI: 10.1044/jshr.3801.174
|View full text |Cite
|
Sign up to set email alerts
|

"No Shoes; They Walked Away?": Effects of Enhancements on Learning and Using Blissymbols by Normal 3-Year-Old Children

Abstract: The present investigation studied the effects of enhancements on the learning, retention, transfer to the unlearned form, and use of Blissymbols in 40 normal 3-year-old children. The subjects, seen individually, learned either 12 standard Blissymbols (SBS) or the same 12 symbols in the enhanced form (EBS). The symbols were introduced with short explanations. The number of trials taken to reach >90% correct identification, the number of symbols selected appropriately to complete a communicative act, the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…This repeated contact with the same symbols may have served to strengthen learning and thus permitted it to be maintained over a period of a month. This is consistent with the idea that learning is reinforced by symbol revision (Raghavendra & Fristoe, 1995). The results also revealed that maintenance was somewhat lower in the 4-year-olds.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This repeated contact with the same symbols may have served to strengthen learning and thus permitted it to be maintained over a period of a month. This is consistent with the idea that learning is reinforced by symbol revision (Raghavendra & Fristoe, 1995). The results also revealed that maintenance was somewhat lower in the 4-year-olds.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, participants had repeated opportunities to reinforce their acquisition and use of symbols over the course of the larger protocol. This is in line with the idea that learning is strengthened and better when the symbols are reviewed after the initial acquisition, iconicity then losing part of its influence with repeated use of the symbols (Raghavendra & Fristoe, 1995).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations